TRADISI MENIKAH PADA HARI RAYA IDUL FITRI DAN IDUL ADHA PERSPEKTIF HUKUM ISLAM - Novi Trianingrum; Masruri Masruri (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2022)
In Islam, marriage can take place on any day, because all days of the year are good days, a marriage is valid if it fulfills the pillars and conditions of marriage. However, in practice, marriages that occur in communities that are still steeped in Javanese customs sometimes still have rules other than those in the terms and conditions of marriage according to Islamic law. This research aims to determine the practice of wedding traditions on Eid al-Fitr and Eid al-Adha in Planjan Village, the views of the people of Planjan Village towards these traditional practices, and to find out the perspective of Islamic law regarding this tradition. This research is field research using qualitative research methods. The data criteria obtained are primary and secondary data. Data was obtained through observation, interviews and documentation. The research results show that the practice of getting married on Eid al-Fitr and Eid al-Adha in Planjan Village is a solution for the community to get around all the complexities of calculations in the Javanese primbon. The results of interviews with 6 sources show that many people in Planjan Village still carry out this tradition. There are those who trust it completely, there are also those who just respect the suggestions of their parents. It all comes back to each individual's beliefs.